Biology - Mader, Sylvia S.; Windelspecht, Michael, 1963- (McGraw-Hill Education SAT subject test, 2019)
Biology is a traditional, comprehensive introductory biology textbook that centers on the evolution and diversity of organisms. Three major themes--evolution, nature of science, and biological systems--are emphasized and integrated throughout the text. -- from publisher's website.